دور التدريب في تطوير مهارات الموظفين في منظمة أطباء بلا حدود في اليمن - مانع عبد الرحمن أحمد; الجماعي تماضر طارق (Journal of Amran University, 2024)
The Role of Training in Developing the Skills of Employees at Médecins Sans Frontières in Yemen. This research in Yemen examined how training affects MSF employees' skills. It found training across all areas (needs assessment, programs, and evaluation) plays a significant role in developing various employee skills. While employee skills were high across the board (acquired, individual, social, organizational, and administrative/creative), the study identified budget limitations as an obstacle to training participation. Interestingly, the organization prioritizes career scholarships, valuing the fresh perspectives external courses offer. Based on the findings, the study recommends increased focus on the training process, including creating annual training plans based on objective assessments of skill gaps. It also emphasizes the importance of recognizing and valuing individual skills and experience as an investment in future organizational excellence.